Role Of the Midwife in The Use of Ultrasonography (USG) Equipment in Antenatal Care (ANC) Service: A Scoping Review - Dini Asrika Devi; Lilik Hanifah; Ana Dwi Prihatiningsih; Andari Wuri Astuti (Universitas Aisyah Pringsewu, 2022)
Ultrasonography (USG) is one of the technological tools in the health sector, especially in midwifery. Midwives are recommended to be able to use technology in the field of midwifery to reduce maternal and child mortality, especially in Indonesia. The aim of this literature study is to determine the role of midwives in the use of ultrasonography (USG) equipment in Antenatal Care (ANC) services. The method used in this literature study is scoping review, the literature search in this study uses 3 health journal databases (PubMed, ProQuest, ScienceDirect). For the selection of articles obtained based on predetermined inclusion and exclusion criteria, using a Prisma Flowchart for the flow of article selection, and doing by critical appraisal using the Mixed Methods Appraisal Tool (MMAT) instrument. The results of the review of a total search of 2,018 articles then found 10 articles that were included in the aim and criteria of the literature study that were set. The articles obtained from various countries consist of quantitative, qualitative, and mix method studies, which obtained 3 themes and 5 sub-themes, namely benefits, curriculum development, and factors that influence the use of ultrasonography (USG) by midwives. It can be concluded that from a review of 10 articles, the need for training and additional curriculum for midwives can use ultrasonography (USG) to determine early pregnancy status and detect abnormalities in a pregnant woman. Abstrak: Ultrasonografi (USG) merupakan salah satu alat teknologi dalam bidang kesehatan khususnya kebidanan. Bidan dianjurkan untuk bisa menggunakan teknologi dalam bidang kebidanan untuk mengurangi angka kematian ibu dan anak terutama di Indonesia. Tujuan dari studi literatur ini untuk mengetahui peran bidan dalam penggunaan alat ultrasonografi (USG) dalam pelayanan Antenatal Care (ANC). Metode yang digunakan dalam studi literatur ini yaitu scoping review, pencarian literatur dalam studi ini menggunakan 3 database jurnal kesehatan (PubMed, ProQuest, ScienceDirect). Untuk sleksi artikel yang didapat berdasarkan kriteria inklusi dan eksklusi yang telah ditentukan, menggunakan Prisma Flowchart untuk alur penyeleksian artikel, serta dilakukannya critical apparaisal dengan menggunakan instrumen Mixed methods Appraisal Tool (MMAT). Hasil review dari total pencarian sebanyak 2.018 artikel, kemudian ditemukan 10 artikel yang masuk kedalam tujuan dan kriteria studi literatur yang ditetapkan. Artikel yang didapat berasal dari berbagai negara yang terdiri dari penelitian kuantitatif, kualitatif, dan mix method study, yang didapatkan 3 tema dan 5 subtema yaitu manfaat, pengembangan kurikulum, dan faktor yang berpengaruh dalam penggunaan ultrasonografi (USG) oleh bidan. Dapat disimpulkan bahwa dari ulasan 10 artikel, perlunya pelatihan dan penambahan kurikulum untuk bidan bisa menggunakan ultrasonografi (USG) guna untuk mengetahui secara dini status kehamilan dan deteksi kelainan pada wanita hamil.